THE ENERGY TRANSFER BETWEEN PRIMARY PRODUCTION AND FISH YIELD IN THE TROPICAL REGION - An, Nguyen Tac; Son, Vo Duy (Vietnam Journal of Marine Science and Technology, 2007)
Some basic issues on the energy transfer between primary production and fish yield in the tropical region were mentioned. In which some remarks on energy flow of autotrophic level, primary production-meso zooplankton, and the ability to construct a general model for the East Sea of Vietnam with simple parameters were discussed. Carbon flow, Pauli Christensen, and Ecopath-Ecosim model were used to verify the trophic level of fish in the coastal zone of Vietnam.